Animal Transportation: Process, Challenge and its Effect on Small Ruminant - Arie Febre Trisiana; A Destomo; F Mahmilia (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2021)
Livestock transportation  is carried out to fullfill the need for consumption as well as for raising the livestock in other areas. The regulation of livestock transportation has not been well implemented yet, and far from the ideal way of livestock transportation, such as the aspects of animal welfare. This paper aims is to  describe the transportation process, challenge and its effects on small ruminants. The process of transporting livestock is carried out by preparing the animals that are going to be transported, and the means of transportation used. Travel distance and road infrastructure conditions provide an affordable connection for the transportation of livestock. Long distances and poor infrastructure conditions can cause stress problems to livestock transportation. Livestock becomes stress and cortisol levels increased in the blood and physiological responses  were affected due to transportation. The Goat Research Institute designed a cage in a truck to transport goats and logistical needs during the trip by land and sea routes.  This type of cage has been used in the distribution of goats to several areas and the journey took 1 to 16 days with average goat mortality rate was about 0.3%. Severe impacts during the trip can be overcome by transporting goats with attention to the transportation system and to ensure the welfare of animals during the trip.